Inclusive Leadership, Trustworthiness, and Trust in Leaders on Organizational Citizenship Behaviour - Zamzami Sabiq; Amiartuti Kusmaningtyas; Sumiati (Pusat Penerbitan dan Publikasi Ilmiah, FEB, Universitas Muslim Indonesia, 2026)
This study aims to prove and analyze the influence of Inclusive Leadership and Trustworthiness on Organizational Citizenship Behaviour (OCB) with Trust in Leaders as a mediating variable among employees of the Scout Movement Quarters (Kwartir Gerakan Pramuka) throughout East Java. This research employs a quantitative approach with a causal explanatory design. The population in this study comprises 144 employees of the Scout Movement Quarters throughout East Java. The sampling technique utilized was total sampling (census method), resulting in a sample of 144 respondents. Data collection was conducted using Google Forms and measured using a Likert scale. The data analysis technique utilized Structural Equation Modeling (SEM), processed using Partial Least Square (PLS) software and SPSS version 26. The results indicate that: 1) Inclusive Leadership has a significant effect on Trust in Leaders; 2) Trustworthiness has a significant effect on Trust in Leaders; 3) Trust in Leaders has a significant effect on Organizational Citizenship Behaviour (OCB); 4) Trust in Leaders significantly mediates the effect of Inclusive Leadership on Organizational Citizenship Behaviour (OCB); and 5) Trust in Leaders significantly mediates the effect of Trustworthiness on Organizational Citizenship Behaviour (OCB).